The economics book - Kishtainy, Niall (New York DK Pub, 2012)
"Reveals the many ideas and schools of economics that have emerged since trading first began in ancient times."--Front jacket flap
Let the trading begin: 400 BCE-1770 CE -- The age of reason: 1770-1820 -- Industrial and economic revolutions: 1820-1929 -- War and depressions: 1929-1945 -- Post-war economics: 1945-70 -- Contemporary economics: 1970-present
Includes index
1
Keywords: Economic history; Economics; Economists